2017
DOI: 10.3390/app7101009
|View full text |Cite
|
Sign up to set email alerts
|

B4C-Al Composites Fabricated by the Powder Metallurgy Process

Abstract: Featured Application: Neutron absorber materials are used in spent-fuel storage racks, storage, and transportation casks to control the reactivity of spent nuclear fuel, allowing the storage and shipment of spent fuel at maximum packing density. Due to the large thermal neutron absorption cross-section of the nuclide B-10 and the excellent mechanical performance of aluminum, B 4 C-Al composites have the potential to serve as the neutron absorber as well as the structural function in fuel racks. This work provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Zhang et al 18 observed that the yield and tensile strength of their 15% and 20% B 4 C reinforced aluminum MMCs increased significantly with increasing B 4 C particle ratio. Poovazhagan et al 19 found that SiC and B 4 C nanoparticle reinforcement significantly reduced the ductility and impact strength of the AA6061 matrix, while remarkably increasing the hardness and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 18 observed that the yield and tensile strength of their 15% and 20% B 4 C reinforced aluminum MMCs increased significantly with increasing B 4 C particle ratio. Poovazhagan et al 19 found that SiC and B 4 C nanoparticle reinforcement significantly reduced the ductility and impact strength of the AA6061 matrix, while remarkably increasing the hardness and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Powder metallurgy is also a very efficient method applied in the recycling of metals and alloys [6]. It should also be noted that the process utilizes temperatures below the melting point of the treated material [7]. Therefore, in the process of fabricating Al/SiC composites using the powder metallurgy method, due to the low sintering temperature, the interfacial reactions between Al and SiC that cause the formation of the brittle Al 4 C 3 phase, which can degrade mechanical properties, are limited [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in SSM, the fabrication process is not promising for applications because of its limitations in the complexity and size of the samples and high costs. For recent decades, powder metallurgy (PM) which belongs to the method (i) has been extensively used for contributing to the distribution of nanoparticles, the PM process shows no typical segregation phenomena compared with other processes, but it shows potential advantages [28][29][30]: (a) Avoiding the harmful reactions between the matrix and the nanoparticles. (b) Enabling to produce AMCs with a high-volume fraction of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%